Combining plant–frugivore networks for describing the structure of neotropical communities. Issue 2 (6th December 2017) - Almeida, Adriana de; Mikich, Sandra Bos
Abstract : Frugivory and seed dispersal are key processes for the maintenance of biodiversity. This is particularly true in the Neotropics, where most plant species depend on animals to disperse their seeds and most birds and mammals include fruits in their diets. We performed a continental‐scale literature review to build a database of interactions between neotropical fruits and fruit‐eating birds and mammals. Our objective was to evaluate the viability of combining literature data from different studies to describe the structure of highly diverse fruit–frugivore neotropical communities. We investigated sites that had been the focus of studies of at least four different avian and/or mammalian taxonomic orders and we included in our database only those conducted for at least a 6‐month period in order to account for the seasonality in fruit availability. In spite of a large number of study sites investigated for frugivory (n = 156), we found a huge gap in the knowledge of community‐wide fruit–frugivore interactions in the Neotropics, since most studies focused on single or a few species. Nevertheless, we were able to construct diverse plant–frugivore qualitative networks for 17 areas unevenly spread throughout the neotropical region. Using complex network analyses, we found that these networks were highly informative and non‐randomly organized. Most networks were both significantly nested and modular, characteristics related to stability and resilience in biological systems. We concluded that it is possible to use merged data to build networks for sites of conservation interest. The main advantage of using this approach is to optimize resources, avoiding exhaustive, costly and time‐consuming fieldwork when data is already available. Whilst bearing in mind the shortcomings of this methodology, these results can be used in studies aiming to understand the ecological processes structuring different communities in the neotropical region and to support conservation and restoration actions.